2018
DOI: 10.17763/1943-5045-88.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Racial (Mis)Match in Middle School Mathematics Classrooms: Relational Interactions as a Racialized Mechanism

Abstract: While research has consistently shown the positive effects of having a teacher of the same race on various student outcomes, the literature has not examined how racial match affects the everyday interactions within classrooms. This research article by Dan Battey, Luis A. Leyva, Immanuel Williams, Victoria A. Belizario, Rachel Greco, and Roshni Shah addresses this underexplored area by documenting relational interactions in classrooms to find one mechanism that could be producing racialized effects on learning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Reading and mathematics (Battey et al , 2018; Gershenson et al , 2016; Rosenbaum, 2020) were identified as weed-out subjects for black children as early as elementary grades. A widely spread statement alleges, “The prison industrial complex will look at the test scores of a city’s third grade population,” […] “if the test grades are low, they know that they’ll have to start building a prison” (Michele Noris as cited in Hudson, 2012, July 2).…”
Section: From Miseducation To Incarceration To Death: a Brief Literat...mentioning
confidence: 99%
“…Reading and mathematics (Battey et al , 2018; Gershenson et al , 2016; Rosenbaum, 2020) were identified as weed-out subjects for black children as early as elementary grades. A widely spread statement alleges, “The prison industrial complex will look at the test scores of a city’s third grade population,” […] “if the test grades are low, they know that they’ll have to start building a prison” (Michele Noris as cited in Hudson, 2012, July 2).…”
Section: From Miseducation To Incarceration To Death: a Brief Literat...mentioning
confidence: 99%
“…Partee (2014) found evidence that teachers of color tended to be more dedicated to the overall success of students of color than White teachers. Teachers of color have been shown to hold more positive perceptions of the academic performance and behavior of students of color than White teachers (Lindsay & Hart, 2017;Wright, 2015), a pattern that holds in studies comparing Black teachers to non-Black teachers as well (Battey et al, 2018;Fish, 2017;Gershenson et al, 2018). Fish (2017) studied referrals for special education services among a diverse sample of teachers using vignettes of fictional case studies about Black students as well as Latino/a students whose English Learner status was manipulated.…”
Section: Benefits Of Black Teachersmentioning
confidence: 99%
“…Second, special education teachers play a direct role in evaluating students, designing and managing their IEPs, and determining the extent to which they are given access to general education classrooms (Girvan et al, 2017;Skiba et al, 2011). Third, with evidence that race is associated with teachers' expectations (Battey et al, 2018;Fish, 2017Fish, , 2019Gershenson et al, 2018) and that subjective diagnoses (e.g., learning disabilities; see Sleeter, 2018) are particularly likely to lead to Black boys' assignment to special education (Harry & Klinger, 2014;Skiba & Williams, 2014), recruitment of teachers who reflect the cultural background of their students for special education teaching jobs is highly important. Beyond rectifying Black students' disproportionate identification for special education services, the cultural competence of BMSETs could increase the effectiveness of the types of services and supports given to Black students receiving special education services.…”
Section: Benefits Of Black Teachersmentioning
confidence: 99%
“…Educators and policymakers need to know the pitfalls of education statistics and data because bad stats engender implicit biases and explicit racism. Earlier this year, a study found that White teachers were three times more negative with Black students (Battey et al 2018). A lot of teachers have negative perceptions of Black students because we continue to use the BS to shape the narrative and, ultimately, the fate of Black children who just need a good education.…”
Section: The Problem With Bsmentioning
confidence: 99%